2014
DOI: 10.2109/jcersj2.122.737
|View full text |Cite
|
Sign up to set email alerts
|

Mesocrystals and Their Related Structures as intermediates between single crystals and polycrystals

Abstract: Generally, mesocrystals are known to be biological and bio-inspired mesoscale structures consisting of oriented nanometric crystalline units. In this article, mesocrystals are broadly categorized in a new family of crystalline materials as intermediate states between single crystals and polycrystals regardless of their unit size and degree of crystalline order. Here, the formation routes and the specific properties of a variety of mesocrystals and their related structures are described. Moreover, the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 141 publications
0
8
0
Order By: Relevance
“…[53] Mesoporouss emiconductors with higherc onductivity and electron mobility will provideaseries of application of energy harvesting andc onversion among solar fuel, photocatalysis, and electricale nergy storage technologies. [53] Mesoporouss emiconductors with higherc onductivity and electron mobility will provideaseries of application of energy harvesting andc onversion among solar fuel, photocatalysis, and electricale nergy storage technologies.…”
Section: The Applicationo Fm Esocrystalsmentioning
confidence: 99%
See 2 more Smart Citations
“…[53] Mesoporouss emiconductors with higherc onductivity and electron mobility will provideaseries of application of energy harvesting andc onversion among solar fuel, photocatalysis, and electricale nergy storage technologies. [53] Mesoporouss emiconductors with higherc onductivity and electron mobility will provideaseries of application of energy harvesting andc onversion among solar fuel, photocatalysis, and electricale nergy storage technologies.…”
Section: The Applicationo Fm Esocrystalsmentioning
confidence: 99%
“…Over years, mesocrystals worked as biological and bio-inspired mesoscale structures consistingo fo riented nanocrystalline units. [53] Mesoporouss emiconductors with higherc onductivity and electron mobility will provideaseries of application of energy harvesting andc onversion among solar fuel, photocatalysis, and electricale nergy storage technologies. [6] In aw ide range of mesocrystals, that is, CaCO 3 [6,54] With controllable formation of TMCs through topotactic transformation, [15e, f] hydrothermal/solvothermalm ethod, [15b, d, 17a, c, d, 18, 19] and growth on supports, [55] there is particular attention paid to potentiala pplicationsi n lithium ion batteries, photocatalysis, enzymei mmobilization, [15d] and antireflection materials.…”
Section: The Applicationo Fm Esocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrothermal synthesis, which includes the use of supercritical water, and aqueous solution based solgel and precipitation methods are widely used for the synthesis of ceramics with controlled structure. There are some reports on ceramic synthesis by bio-inspired and bio-mimetic processes, which are performed using water as a solvent below 373 K. 1) Recently, computational simulation reveals that water not only acts as a solvent, but also has a dynamic effect on crystal formation.…”
Section: Introductionmentioning
confidence: 99%
“…18−30 Our groups 19,20 showed that the biogenic CaCO 3 crystals are composed of bridged nanograins that are arranged in the same crystallographic direction. A nanocluster structure with well-aligned small crystal domains on spicules of a sponge was revealed by atomic force microscopic and transmission electron microscopic investigation.…”
Section: ■ Introductionmentioning
confidence: 99%